PENGEMBANGAN SUMBER BELAJAR DIMOOCS PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DISMP NEGERI 6 MAKASSAR - A.Fauziah; Abdul Hakim; Nurhikmah H (STKIP Subang, 2026)
The application of technology in education is growing with the advent of various digital platforms, one of which is Massive Open Online Courses (MOOCs), which allow students to access learning materials flexibly. This research aims to develop learning resources in MOOCs for Pancasila and Civics education that can motivate students in learning, using the Alessi and Trollip development model. This model consists of several stages: planning, design, and development. During the planning stage, teachers are identified to determine learning needs relevant to students and the applicable curriculum. The design of learning materials focuses on developing interactive learning resources that utilize multimedia and are easily accessible to students. . The implementation of the MOOCs platform shows that students are more interested and involved in technology-based learning that provides various learning formats such as videos, quizzes and online discussions. The subjects in this study were 20 students and 1 teacher of Pancasila and Citizenship Education. Data collection used interviews with teachers, content/material expert validation questionnaires, media expert validation questionnaires, beta test questionnaires 1 (small group test), beta test questionnaires 2 (large group test), and other supporting documents in this study. The data analysis techniques used consisted of qualitative descriptive techniques and static descriptive techniques. The results of this study indicate that the results of interviews with teachers indicate that students find it easier to understand learning through technology compared to existing real learning resources. The results of the product feasibility assessment through the alpha test on content/material experts were 100% (very valid) and on media experts 93.75% (very valid). Furthermore, in beta test 1 (small group), the score was 79.69% (practical) and in beta test 2 (large group), the score was 84% ​​(practical). Based on these analysis results, it was concluded that the development research produced a MOOCs platform product that was valid and practical for use in the learning process.